P-022 Relationship between sperm movement characteristics assessed by a sperm motility analysis system (SMAS) and normal fertilization rates in vitro. (30th June 2022) - Harada, Y; Fukunaga, E; Shiba, R; Ikeda, M; Okano, S; Kinutani, M
Abstract: Study question: Is there a relationship between movement characteristics of human sperm assessed by SMAS and normal fertilization rates in vitro? Summary answer: The curvilinear path wobble of motile sperm before insemination is predictive of normal fertilization rates after in vitro fertilization (IVF). What is known already: Assessment of semen parameters is very important in both the diagnosis of male infertility and the selection of methods for treatment with conventional-IVF (C-IVF) or intracytoplasmic sperm injection (ICSI). Several studies have reported that objectively movement characteristics of motile sperm assessed by SMAS are related to the functional capacity of human sperm. However, there are no established the objective indicators and criteria for sperm motility characteristics assessed by SMAS. In this study, we investigated the utility of the movement characteristics of motile sperm measured by SMAS as an indicator of normal fertilization rates. Study design, size, duration: Retrospective experimental trial conducted in a single IVF center between January 2018 and February 2020. Sperm movement characteristic analysis was performed using the SMAS in 300 IVF cycles using sperm from 270 men. At least three metaphase II oocytes were inseminated in C-IVF. The SMAS estimates were measured in semen and before insemination. This study was approved by the Ethics Committee of the Institutional Review Board (IRB) of Kinutani Women's Clinic, Hiroshima, Japan. Participants/materials, setting, methods: Motile sperm from at least 3 different fields were observed in each sample and their parameters were examined. First, we investigated the correlation between the normal fertilization rates and sperm motility characteristics. Next, the group comprising 300 cycles was classified into a group of a ≥ 60% normal fertilization (group 1: 229 cycles) and a group with <60% normal fertilization (group 2: 71 cycles) to assess the sperm characteristics described below. Main results and the role of chance: The following indicators were evaluated: amplitude lateral head displacement (ALH), best cross frequency (BCF), curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP), linearity (LIN=VSL/VCL), straightness (STR=VSL/VAP), and curvilinear path wobble (WOB=VAP/VCL).There were significant correlations between normal fertilization rates and semen parameters, including VCL (r = 0.014; P < 0.05) and ALH (r = 0.177; P < 0.05). However, there were no significant correlations for other parameters. Moreover, there were no significant correlations between normal fertilization rates and sperm parameters before insemination. The SMAS estimates in semen and sperm before insemination were compared between group 1 and group 2. There were no significant differences in most baseline characteristics across groups, except for the number of normally fertilized oocytes. However, there were significant differences in sperm WOB before insemination between group 1 and group 2 (0.589 vs. 0.572; P < 0.05). Sperm motility before insemination was more curvilinear in group 1 than in group 2. The optimal cut-off value for WOB of motile sperm before insemination for predicting≥60% normal fertilization was 0.587 (AUC was 0.60; P < 0.05). These results were suggested that the WOB of sperm before insemination is useful as an indicator in determining the selection of methods for fertilization in vitro. Limitations, reasons for caution: The main limitations of this study are its retrospective design and small sample size. A prospective study is necessary to further clarify the prediction criteria. Wider implications of the findings: This study suggests that the WOB of motile sperm before insemination may be used as one of the indicators to predict good fertilization rates after C-IVF. Trial registration number: N.A.